PERANAN LAGU POPULAR MINANGKABAU SEBAGAI PENYUMBANG PENGEMBANGAN PARIWISATA DAERAH DI INDONESIA to the Local Tourism Development in Indonesia - Eva Krisna (Balai Bahasa Sumatra Barat, 2015)
Tourism is one part of the creative industry that can be developed in Indonesia as a choice of earning foreign exchange beside oil and natural gas. Indonesian tourism industry has bigopportunity and challenge compared to the world tourism. Tourism products is not just nature, but also culture, adventure, living environment, and culinary. Culinary becomes one of thetourism icons for every place in the world, such as: England with scones, Singapore has fishball noodles, and Malaysia with nasi kandar. Indonesia also has many kinds of culinaryicons in every regions, such as bakpia in /Ý•Å¿ßO•—nî?;ßO•—ur in Jakarta, bika ambon in Medan, and balado chips in Padang. There was a unique way in promoting culinary in WestSumatera in the past. The people used to sing in selling the culinary product, its tradition was called bajojo. This bajojo tradition continued to be folk songs and then recorded commercially. Bajojo culinary song is a part of literature, it belongs to spoken literature. The bajojo songs are existing through the industrial and technological recording and become the popular songs in West Sumatera. About thirty recording houses are actively producing tens of recordingtitles in cassette and CD